2018
DOI: 10.1155/2018/5784902
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Experiences and Sexual Topics Discussed with Adolescents in the Accra Metropolis, Ghana: A Qualitative Study

Abstract: Background. Traditionally, discussion about sexuality is subdued in proverbs and is earmarked for adults. However, adolescents also need information about their sexuality to make informed choices regarding sexual behaviours. This study, therefore, seeks to explore the experiences of parents discussing sexuality topics with adolescents in the Accra Metropolis, Ghana. Methods. This was a qualitative study that used focus group discussions (FGDs) and in-depth interviews (IDIs) to assess parents’ experiences in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 24 publications
(45 reference statements)
8
29
0
Order By: Relevance
“…Our study highlights gaps in parent-child communication of sexual and reproductive health matters. We found that majority of adolescents had never discussed sex-related matters with their parents/caregivers and this is consistent with reports from similar studies [11,17]. However, a few adolescents reported they have had SRH discussions with their mothers; though not statistically significant, more girls reported having had this discussion with mothers, compared to boys.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our study highlights gaps in parent-child communication of sexual and reproductive health matters. We found that majority of adolescents had never discussed sex-related matters with their parents/caregivers and this is consistent with reports from similar studies [11,17]. However, a few adolescents reported they have had SRH discussions with their mothers; though not statistically significant, more girls reported having had this discussion with mothers, compared to boys.…”
Section: Discussionsupporting
confidence: 91%
“…In-depth exploration of the contents and triggers of parent-child communication revealed that discussions often centred on pubertal changes, relationship with opposite sex, abstinence from premarital sex, and teenage pregnancy and abortion, and were triggered by environmental factors such as unpleasant or tragic occurrences in the community and parental observations of budding relationships between adolescents of opposite sex. The content and triggers of sexual and reproductive health (SRH) discussions between parents and their children in this study also corroborate findings from similar studies [11,17]. The scope of discussion between parents and their adolescents was found to be limited and this could explain why adolescents would prefer to discuss with their peers and friends who are 'open-minded', rather than their parents.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations